2021
DOI: 10.37506/ijphrd.v13i1.17321
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge on COVID-19 among Nursing Students of a Selected Nursing Institute of Dhaka City, Bangladesh

Afroza Akhter,
Bilkis Banu,
Nasrin Akter
et al.

Abstract: Background: Bangladesh is trying to shape out coronavirus disease of 2019 (COVID-19) pandemic with limited frontiers resources science March 2020. Among all frontier, Bangladeshi nurses are also playing a dynamic role to control infection through direct contact with COVID patients.Objective: This research aims to identify the level and predictors of poor knowledge of nursing students toward the COVID-19.Method: This study was a quantitative type of cross-sectional study with 150 participants randomly selected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 10 publications
(11 reference statements)
0
1
0
Order By: Relevance
“…Indirectly COVID-19 outbreaks adversely affect the condition of children like disruption to their healthcare, nutrition, protection, education and overall mental wellbeing, vaccinations and preventive and curative services. Globally, in the pandemic era it was massively found that the level of knowledge plays an important role in enhancing the transmission of corona virus [6]. The primary reports of COVID-19 infection notify that the rarity of sickness in infants, including only 9 young people under the age of 14.…”
Section: Introductionmentioning
confidence: 99%
“…Indirectly COVID-19 outbreaks adversely affect the condition of children like disruption to their healthcare, nutrition, protection, education and overall mental wellbeing, vaccinations and preventive and curative services. Globally, in the pandemic era it was massively found that the level of knowledge plays an important role in enhancing the transmission of corona virus [6]. The primary reports of COVID-19 infection notify that the rarity of sickness in infants, including only 9 young people under the age of 14.…”
Section: Introductionmentioning
confidence: 99%